Public perception of the lifetime morbid risk of mental disorders in the United States and associations with public stigma - Lawson, Nicholas D. (Springerplus, 2016)
PURPOSE: This study examined the relationship between estimates of the prevalence of mental disorders and mental health stigma. It also examined whether stigma might be more greatly associated with the terms “mental illness,” “mental disorder,” or “mental health condition.” METHODS: Respondents (N = 302) on Amazon’s Mechanical Turk completed an online survey designed to measure social distance, which is one variant of stigma. Half of the respondents were informed at the beginning of the survey that the lifetime morbid risk (LMR) of meeting criteria for at least one mental disorder at some point in life was 70–80 %, while the others were asked to provide their own LMR estimates. All respondents were also randomly assigned to view the survey with either the term “mental illness,” “mental disorder,” or “mental health condition.” RESULTS: Higher LMR estimates (B = −0.030; β = −0.154), having a mental disorder (B = −2.002; β = −0.200), and a history of contact with an individual with a mental disorder (B = −2.812; β = −0.298), each significantly predicted lower desire for social distance. Respondents in the “mental disorder” group endorsed greater desire for social distance. Participants who were informed about LMR at the start of the survey did not score lower on social distance. CONCLUSIONS: Estimates for LMR were more than half as predictive of social distance scores as contact with individuals with mental disorders. But anti-stigma interventions may need to do more than inform individuals about the high prevalence of mental disorders in order to be effective. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s40064-016-2974-y) contains supplementary material, which is available to authorized users.